Effects of Charge Motion, Compression Ratio, and Dilution on a Medium Duty Natural Gas Single Cylinder Research Engine - Wheeler, Jennifer; Stein, Joshua; Hunter, Gary (SAE International journal of engines, 2014)
Recent advances in natural gas (NG) recovery technologies and availability have sparked a renewed interest in using NG as a fuel for commercial vehicles. NG can potentially provide both reduced operating cost and reductions in CO₂ emissions. Commercial NG vehicles, depending on application and region, have different performance and fuel consumption targets and are subject to various emissions regulations. Therefore, different applications may require different combustion strategies to achieve specific targets and regulations. This paper summarizes an evaluation of combustion strategies and parameters available to meet these requirements while using NG in a spark ignited engine. A single-cylinder research engine using a modified diesel cylinder head was employed for this study. Both stoichiometric combustion with cooled exhaust gas recirculation (EGR) and lean-burn were evaluated. Testing quantified the effects of dilution (EGR or excess air), swirl ratio, and compression ratio on the operating limits, engine-out emissions, and fuel efficiency at operating conditions typical for heavy-duty vehicle applications. The data acquired indicates that lean-burn is a viable option for moderate NOx emission applications such as Euro IV and V. Stoichiometric combustion enables the use of a three way catalyst which provides low tailpipe NOx as required for more stringent standards. Stoichiometric combustion with cooled EGR enabled greater full load torque capability than lean combustion, but lean combustion provided improved fuel efficiency. In both cases, higher compression ratio resulted in an increase of efficiency but reduced full load capability, and increased swirl extended the dilution capability.